Abuso sexual Infantil como factor de riesgo de los trastornos de la conducta alimentaria en adultos. - Masache Vega, Dámaris Cristina (2023)
Childhood sexual abuse is one of the traumatic events with the greatest impact on the development of psychopathologies in adulthood. Several research have observed the effect of this event on disordered and compulsive eating behavior in order to find relief from the psychological processing of childhood trauma. The principal objective is to analyze childhood sexual abuse as a risk factor for eating disorders in adults. This was a bibliographic study in which 38 articles were selected from scientific databases such as Scopus, Research Gate, ProQuest, PubMed and Google Scholar, and evaluated with the Critical Review Form- Quantitive Studies (CRF-QS) instrument, which determined their methodological quality. Results explains that individuals who experienced sexual abuse in childhood tend to have disordered eating behaviors centered on binge eating/purging as a regulatory mechanism for psychological stress, thus becoming diagnosed with clinical condition of Bulimia Nervosa, Binge Eating Disorder, and Binge Purging Anorexia Nervosa, in adulthood. In conclusion, childhood sexual abuse is a significant risk factor in the development of ED in adults who show binge/purge as the main symptom, since it is explained that emotional eating represents a regulatory mechanism of the psychological stress caused by the trauma; this also determines a greater difficulty to achieve complete recovery and increases the appearance of psychiatric comorbidities that complicate the clinical picture in adults with ED.